LES of Flow past Circular Cylinder at Re = 3900 - B.N Rajani; A Kandasamy; Sekhar Majumdar (Journal of Applied Fluid Mechanics, 2016)
Transitional flow past a circular cylinder in the lower subcritical regime (Re = 3900) has been analysed using Large Eddy Simulation (LES) coupled to Smagorinsky and dynamic sub grid scale models. These simulations have been carried out using a parallel multiblock structured finite volume code which is based on SIMPLE algorithm. The predictions are validated against detailed measurement data for mean as well as turbulence quantities. The present LES prediction in general agree reasonably well with the measurement data in the near wake region but deviates from the measurement data in the far wake region which may be due to the coarse resolution of the grid in this region. The influence of the SGS model on mean flow quantities as well as on the flow structures are also discussed.